Exploring refugees’ health care access in times of COVID-19: a quantitative study in the Lisbon region, Portugal - Portela, Vanessa; Hamwi, Sousan; Oliveira Martins, Maria R. (Frontiers in Public Health, 2024)
Background To address the health needs of refugees, health services must be culturally competent and facilitate this population’s access to health care, especially in the context of a pandemic. However, to the extent of our knowledge, there are no published quantitative studies exploring refugees’ access to health care during the pandemic in Portugal. The objective of this study is to describe the demographic and socioeconomic characteristics of refugees living in Lisbon and to explore their healthcare access patterns during the COVID-19 pandemic. Methods We conducted a cross-sectional, descriptive, and quantitative study from May to November 2022. Using Levesque’ s theory on health care access, we designed and applied a 38-item questionnaire through face-to-face interviews with refugees living in Lisbon for at least 12 months, and used descriptive statistics to characterize sociodemographic and healthcare access profiles during the pandemic. Results The mean age of the 36 recruited refugees was 35 years (SD=10.24), the majority were male (56%), married (72%), had at least a secondary education (69%), were unemployed (77.8%), and had a median length of stay in Portugal of 17 months. The majority never tested positive for the coronavirus (58%) and one out of the positive was admitted to hospital due to severe COVID-19. A total of 97% received COVID-19 vaccination, of which 69% had an incomplete schedule. A quarter did not have access to information about COVID-19 in a language they understood, and although 97% needed health care during the pandemic, more than half (63%) did not seek it because of structural and cultural barriers. Only 18.2% sought counseling services. A total of 58.8% felt like healthcare professionals did not always show respect towards their culture, and 64.7% reported that healthcare professionals did not always discuss treatment options with them. Conclusions This study’s findings highlight the need to endow inclusive communication, cultural competency, and patient involvement in health care. Identified population characteristics and barriers to health care access in this study may inform future research on the health care needs of refugees in Portugal and ultimately assist in the devising of strategies to reduce inequalities in health care access.